Implementasi Quantum Teaching Pada Pembelajaran Tematik Kelas V MI Mambaul Ulum Kandangrejo - Faiqotul Isma Azizah; Hartono Hartono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Jember, 2021)
The Quantum Teaching learning model is a modification of the various interactions that exist in and around the moment in learning. This study aims to find out more about how to apply Quantum Teaching in measuring students' abilities including cognitive, affective and psychomotor aspects. This research method uses qualitative research methods with the type of research field research. Data collection techniques using observation techniques, interviews, and documentation. While the data analysis is a qualitative analysis model of Miles and Huberman and Saldana which consists of data collection, data condensation, data presentation and drawing conclusions. The results of this study are: (1) Implementation of Quantum Teaching in Class V Thematic Learning at MI Mambaul Ulum Kandangrejo cognitive aspects, namely students are able to think more critically and broadly, students are able to do assignments or exercises and can understand learning well, students able to provide questions and answers properly and appropriately. (2) Implementation of Quantum Teaching in Class V Thematic Learning at MI Mambaul Ulum Kandangrejo aspects in the affective aspect, namely: the curiosity of students increases, students become more focused, students' attitudes become more confident and courageous. (3) Implementation of Quantum Teaching in Class V Thematic Learning at MI Mambaul Ulum Kandangrejo psychomotor aspects, namely: students are able to practice well the learning media is provided, students are able to name the names and parts of the circulatory organs, students are able to show the circulatory organs blood using the medium. Keywords: Quantum Teaching; Learning; Madrasah Ibtidaiyah Model pembelajaran Quantum Teaching merupakan pengubahan bermacam-macam interaksi yang ada di dalam dan di sekitar momen dalam pembelajaran. Penelitian ini bertujuan untuk mengetahui lebih dalam bagaimana penerapan Quantum Teaching dalam mengukur kemampuan peserta didik meliputi aspek kognitif, afektif dan psikomotorik. Metode penelitian ini menggunakan metode penelitian kualitatif dengan jenis penelitian Field Research. Teknik pengumpulan data menggunakan teknik observasi, wawancara, dan dokumentasi. Sedangkan analisis data analisis kualitatif model Miles dan Huberman dan Saldana yang terdiri dari pengumpulan data, kondensasi data, penyajian data dan penarikan kesimpulan. Hasil penelitian ini yaitu: (1) Implementasi Quantum Teaching Pada Pembelajaran Tematik Kelas V di MI Mambaul Ulum Kandangrejo aspek kognitif yaitu peserta didik mampu berfikir secara lebih kritis dan luas, peserta didik mampu mengerjakan tugas atau latihan dan dapat memahami pembelajaran dengan baik, peserta didik mampu memberikan pertanyaan dan jawaban dengan baik dan sesuai. (2) Implementasi Quantum Teaching Pada Pembelajaran Tematik Kelas V di MI Mambaul Ulum Kandangrejo aspek dalam aspek afektif yaitu: rasa ingin tahu peserta didik meningkat, peserta didik menjadi lebih fokus, sikap peserta didik semakin percaya diri dan berani. (3) Implementasi Quantum Teaching Pada Pembelajaran Tematik Kelas V di MI Mambaul Ulum Kandangrejo aspek dalam aspek psikomotorik yaitu: peserta didik mampu mempraktikkan dengan baik media pembelajaran disediakan, peserta didik mampu menyebutkan nama dan bagian organ peredaran darah, peserta didik mampu menunjukkan bagian organ peredaran darah dengan menggunakan media. Kata Kunci: Quantum Teaching; Pembalajaran; Madrasah Ibtidaiyah